Having Your Cake: Caricaturing the Business Organization in 20th-century and Contemporary American Art and Poetry - David Reckford (European Journal of American Studies)
We focus here on the idea of business as a trope and as a reality that can be placed in a rhetorical position in art (mostly visual art and poetry) in the 20th century. Many artists, from Henri Matisse to Marc Rothko, have turned their heads away from the business organization, although it is a cornerstone of society in the modern capitalist era; conversations with the business world have indeed been a taboo for artists of the avant-garde particularly, which explains why some artists have been taking the contrarian position of making business part of their subject. Business is the utilitarian funneling of resources into standardized and marketed output, with its hated by-products including the organization man, and the daily grind. For many, big business is the source of those greatest of today’s problems: irreversible pollution and climate change. Part of being a progressive-spirit modernist is to open up the form to new fields of experience. In 1919, Marianne Moore, in a Duchampian gesture, broached the inclusion of utilitarian language into poetry. After that other poets, novelists, and especially visual artists have turned their gaze and their rhetoric towards what might be called the business blind spot in art, to expand art’s demesne dialectically, to engage in subtle social criticism, to reach behind business to get to society or, fascinatingly, in the cases of Andy Warhol, and later Jeff Koons, to create new ambiguities that play on contemporary anxieties, revealing hidden vulnerabilities in modern societies, to those that can see and feel them.